Growth and Yield of Rabi Sorghum as Influenced by Soil and Water Conservation Structures - Mallappa, M; Radder, G D; Manjunath, S (Annals of Arid Zone, 2016)
Investigation carried out to know the impact of soil and water conservation structures on soil moisture, growth and yield of rabi sorghum revealed that the soil moisture was more in levelled portion of zingg terrace, graded zingg terrace and contour border strip treatments. Plant height, total dry matter production and its distribution into leaf, stern and reproductive parts, leaf area index (LAI), leaf area duration (LAD), crop growth rate (CGR), net assimilation rate (NAR) and specific leaf weight were significantly higher in contour border strip, zingg and graded zingg terrace and increased the grain yield by 103.6, 105.0 and 94.8 % during the first and 101.8 and 112.4, 110.5% during the second years over the control.